In Vitro Antihelmintic Activity of the Hydroethanolic Leaf Extracts of Avicennia marina (White Mangroves) on Eudrilus eugeniae (African Nightcrawlers) (American Journal of Life Science and Innovation, 2025)
Research is needed to determine the Avicennia marina hydroethanolic leaf extract is effective against adult E. eugeniae, despite research showing that it can eliminate helminths such as Pheretima posthuma. The purpose of this study was to ascertain the hydroethanolic leaf extracts of A. marina antihelmintic effectiveness against adult E. eugeniae in vitro. Using E. eugenie adults (6–8 cm in length and 0.2–0.3 cm in breadth), the percentage vermicidal activity of three concentrations of dried crude hydroethanolic leaf extract of A. marina, 25, 50, and 75 mg/mL of distilled water, was assessed every three hours for 12 hours. Five replicates, three trials, distilled water as a negative control, and mebendazole as a positive control were all examined. According to the findings, the hydroethanolic leaf extracts of A. marina have shown antihelmintic efficacy against E. eugenie adults in vitro at doses of 50 mg/mL and 75 mg/mL utilizing Kruskal-Wallis and LSD on the 3, 6, 9, and 12 hours, with a p-value of less than .05. In both concentrations, 50 and 75mg/ml, until the 12-hour exposure to the extract, there was no discernible difference between them. In vitro antihelmintic activity was best demonstrated at 50 mg/mL for 3 hours (mean = 91.1; sd = 26.6), and the in vitro antihelminthic activity was significantly superior to that of the positive control for the same duration (mean = 2.22; sd = 8.61). The results scientifically demonstrated the antihelmintic efficacy of hydroethanolic leaf extract of A. marina against E. eugeniae and provided the foundation for testing against Ascaris, Trichuris trichiura, and hookworms.